27-hydroxycholesterol: A novel player in molecular carcinogenesis of breast and prostate cancer. (October 2017) - Marwarha, Gurdeep; Raza, Shaneabbas; Hammer, Kimberly; Ghribi, Othman
Highlights: 27-OHC is a SERM with potential implications in hormonal cancers. 27-OHC exacerbates ER+ breast cancer. 27-OHC increases cell proliferation in prostate cells. 27-OHC is a novel risk factor in hormonal cancers. Abstract: Several studies have suggested an etiological role for hypercholesterolemia in the pathogenesis of breast cancer and prostate cancer (PCa). However, the molecular mechanisms that underlie and mediate the hypercholesterolemia-fostered increased risk for breast cancer and PCa are yet to be determined. The discovery that the most abundant cholesterol oxidized metabolite in the plasma, 27 hydroxycholesterol (27-OHC), is a selective estrogen receptor modulator (SERM) and an agonist of Liver X receptors (LXR) partially fills the void in our understanding and knowledge of the mechanisms that may link hypercholesterolemia to development and progression of breast cancer and PCa. The wide spectrum and repertoire of SERM and LXR-dependent effects of 27-OHC in the context of all facets and aspects of breast cancer and prostate cancer biology are reviewed in this manuscript in a very comprehensive manner. This review highlights recent findings pertaining to the role of 27-OHC in breast cancer and PCa and delineates the signaling mechanisms involved in the governing of different facets of tumor biology, that include tumor cell proliferation, epithelial-mesenchymal transition (EMT), as well as tumor cell invasion, migration, and metastasis. We also discuss the limitations of contemporary studies and lack of our comprehension of the entire gamut of effects exerted by 27-OHC that may be relevant to the pathogenesis of breast cancer and PCa. We unveil and propose potential future directions of research that may further our understanding of the role of 27-OHC in breast cancer and PCa and help design therapeutic interventions against endocrine therapy-resistant breast cancer and PCa.